Pengembangan Media Pembelajaran Berbasis Lingkungan pada Materi Bahasa Arab di Madrasah Tsanawiyah Nurul Jadid Paiton Probolinggo - Firdaus, Sulton; Syauqi, Faiz; Maulidyah, Malihatul (Universitas Nurul Jadid, 2021)
Learning Arabic using environment-based media is a form of bringing students or learners closer to the material being studied with the real world and close to their daily lives so that in the implementation of learning it can suppress students' learning difficulties and is expected to increase the level of achievement of learning objectives. This study aims to develop an environment-based learning media on Arabic material at Madrasah Tsanawiyah Nurul Jadid Paiton Probolinggo. This research method uses a type of development research or commonly referred to as Research and Development. Validators include material experts, Arabic language experts and learning media experts. The results of this study are the learning module on environment-based Arabic language material named “درس اللغة العربية” Class VII Arabic Language Learning, with a product assessment with a validity result of 4.26 (very good) for the assessment of material experts; and 4.35 (very good) for the assessment of linguists and 4.25 (very good) for the assessment of media experts. The results of the assessment through the limited trial stage were 4.30 (very good).